Intradermal Inoculation of Formalin Treated Escherichia Coli Produced Protective Antibody against Protein of Specific Molecular Weight in Mice Model - Farhana Parveen; SM Shamsuzzaman; Sonia Parveen; Kohinur Hasan (International Journal of Scientific Research in Dental and Medical Sciences, 2025)
Background and aim: Escherichia coli can cause serious infections in humans and animals while constituting a significant portion of the microbiota in many hosts. Due to the increasing global prevalence of multidrug-resistant (MDR) E. coli bacteria, it is vital to explore alternate therapeutic approaches, such as vaccines. This study was designed to detect a specific protein based on molecular weight in serum and splenic cell culture supernatant using a formalin-inactivated whole-cell vaccine against multidrug-resistant (MDR) E. coli.Material and methods: This study used MDR E. coli obtained from clinical samples to immunize 15 Swiss albino mice intradermally. Fourteen days after the third immunization dose, mice were injected with live E. coli intraperitoneally and monitored for 14 days. Sera and spleen cell culture supernatants were obtained. E. coli antigens used in vaccine production were sonicated, and their molecular weights were determined by SDS-PAGE. ELISA was used to measure protective antibodies against antigens of different molecular weights.Results: 100% of immunized mice survived after the lethal dose of live E. coli. The experimental group mice's pre- and post-challenge serum and splenic cell culture immunoglobulin G antibodies had noticeably greater optical density (OD) values than the control mice. E. coli proteins ranging from 11 to 17 kDa showed higher OD values in sera and splenic cell culture supernatant.Conclusions: This indicates that E. coli antigens ranging from 11 to 17 kDa are more immunogenic and can be used as a potential vaccine formulation.